Psychometric Properties of Work–Family Enrichment Self-Efficacy Scale: Lithuanian Version - Vadvilavičius, Tadas; Stelmokienė, Aurelija (Psichologija, 2022)
Valid and reliable research methods are needed to assess the work–family enrichment self-efficacy. Two cross-sectional studies were conducted to test the psychometric properties (internal consistency, convergent and/or structural validity) of the Lithuanian version of the work–family enrichment self-efficacy scale. Results revealed that the Lithuanian version of the work–family enrichment self-efficacy scale had high internal consistency. Adequate convergent validity was confirmed by statistically significant positive relationships between work–family enrichment and its dimensions, job satisfaction, and general self-efficacy. Finally, structural validity was confirmed by exploratory and confirmatory factor analyses, that revealed that one factor explained data well. The results of the research confirmed that the Lithuanian version of the work-family enrichment self-efficacy scale was suitable for further research.
Keywords: work–family enrichment self-efficacy; psychometric properties; scale validity; reliability